The future of diversity - Kuptsch, Christiane; Charest, Éric (International Labour Organization, 2021)
In this collection, scholars and practitioners reflect on the most appropriate interventions to create a more inclusive labour market for all. They explore the economic case for diversity and diversity management strategies, finding that diversity and inclusion must go hand in hand. The book also sheds light on the policy dilemma between respecting individuals and countering structural inequalities, which often requires categorization into groups. The authors remind us that there is diversity within diversity: not everyone receiving the same label has the same needs. The book covers a range of issues including gender equality and mainstreaming, migration and ethnic diversity, racism, violence against LGBTI people and age discrimination. It is thus a rich source of inspiration for anyone wishing to move towards greater justice in the labour market.
Keywords: approches et analyses; discipline; identités LGBTQIA2+; inégalités; justice sociale; racisme; rapport; sciences de la gestion; sexisme; systèmes d'oppressions; thématiques; économie

Filles corsaires : écrits sur l'amour, les luttes sociales et le karaoké - Toffoli, Camille (Les éditions du remue-ménage, 2021)
Camille Toffoli croit que les serveuses de diners, les chanteuses country, les sad girls et les championnes de rodéo ont quelque chose de fondamental à nous apprendre sur les rapports de genre et les privilèges de classe. Filles corsaires construit une pensée qui a les deux pieds dans la vie, qui jette son dévolu sur les figures oubliées et les angles morts d’un certain féminisme universitaire. Pourquoi le célibat volontaire, l’autonomie sexuelle et la non-maternité sont-ils toujours frappés de suspicion ? L’amitié peut-elle réellement lutter contre l’hétéronormativité ? Comment penser une politique de la solitude ? L’autrice investigue ces questions, et bien d’autres, à travers une série de portraits où les anecdotes côtoient les réflexions philosophiques. Une éthique féministe inconfortable qui se déploie quelque part entre les journées de travail en librairie, les soirées karaokés et les brunchs deux oeufs-bacon.
Keywords: amériques; approches et analyses; cours; discours dominant; fem5050; genre; identités LGBTQIA2+; justice sociale; lesbianisme; militance; premier cycle; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques